Acceptance of Students with Physical Disabilities in Medical Schools in Saudi Arabia: Perception, Experience, and Recommendation - Batarfi M; Alraddadi A (Advances in Medical Education and Practice, 2024)
Munirah Batarfi,1,2 Abdulrahman Alraddadi1,2 1Department of Basic Medical Sciences, College of Medicine, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 2King Abdullah International Medical Research Center (KAIMRC), Ministry of National Guard – Health Affairs, Riyadh, Saudi ArabiaCorrespondence: Abdulrahman Alraddadi, Department of Basic Medical Sciences, College of Medicine, King Saud bin Abdulaziz University for Health Sciences, P.O. Box: 3660, Riyadh, 11481, Saudi Arabia, Tel +966114295280, Email aalraddadi.2012@gmail.comIntroduction: Physical disability is seen as a burden in many countries, and it has been a challenge to create a healthy environment and a fair living experience for all people with physical disability. For a long time, the number of students accepted to medical school has been limited, and the number of successful experiences for doctors with disabilities is inadequate worldwide. This study aims to investigate the perception of the public, medical educators, and medical students about the acceptance of students with physical disabilities in medical schools in Saudi Arabia.Methods: The study uses two methodological strategies: a quantitative cross-sectional survey and a qualitative interview with a young female doctor with a physical disability to discuss her educational experience and work journey in Saudi Arabia and abroad. The study was conducted at the College of Medicine, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia.Results: The perception survey results showed a broad acceptance of the public, medical educators, and medical students regarding the enrollment of students with physical disabilities in medical schools and regarding being treated by doctors with physical disabilities. The participants also believed that students with physical disabilities are compatible with most doctors’ jobs.Conclusion: Students with physical disabilities should be able to study and practice medicine. Educational and health institutions should apply more effort and commitment to provide the necessary accommodations to accept students and doctors with physical disabilities based on their cognitive ability but not their physical disability.Keywords: medical education, education, medical school, disability, students with physical disabilities